BUSINESS INTELLIGENCE ON SUPPLY CHAIN RESPONSIVENESS AND AGILE PERFORMANCE: EMPIRICAL EVIDENCE FROM MALAYSIAN LOGISTICS INDUSTRY - Kaur , Kashveenjit (International Journal of Supply Chain Management, 2021)
Purpose: This study examine how BIS implementation affects the agile efficiency of the supply chain with the logistics industry's supply chain responsiveness. As a variable for assessing the relationship and effect on agile efficiency, business intelligence competence (managerial competence, technological competence and cultural competence) and supply chain responsiveness will be investigated. Methodology: A survey questionnaire comprised of 39 questions using the purposive method of sampling used to select the target group and replied to the survey with the outcome of a total of 50 respondents, via SPSS, the data was further analysed to examine the relationship between all variables. Findings: The study finds that (1) business intelligence competence has a significant positive impact on the response to the supply chain, (2) business intelligence competence has a significant positive impact on the supply chain's agile performance, (3) responsiveness to the supply chain has a significant positive impact on agile performance. Unique contribution to theory, practice and policy: This study contributes to enhancing the quality and effectiveness of the business operation of the 3PL service provider, government customs and port department.